Intersectionality and feminist activism - Šadl, Zdenka (Teorija in praksa, 2017)
The perspective of intersectionality underlines the fact that oppression in a society has several sources that interact with and overlap each other. Intersectionality is not only an academic project but also forms part of feminist activism. In the first part of the article, we provide a brief overview of feminist waves and intersectionality, along with the design that underpins our study. In the second part, intersectionality is analysed relative to student feminist societies (SFS) operating at 84 universities across the United Kingdom. Our study was conducted by using the interview method - talks with leading SFS members around the United Kingdom - and a survey which included a significantly larger sample of SFS members. The authors conduct a socio-demographic analysis of SFS' members and examine their openness towards minority groups as an indicator of their intersectionality. The vast majority of the societies' members strongly identified with intersectional feminism, while their affiliation with third-wave feminism was considerably lower. Interviews with leading SFS members showed that intersectionality significantly affects their feminist discourse and practices. Although the societies are open to minority groups, room for improvement remains.
Keywords: aktivizem; družbene manjšine; Feminism; feministična društva; Feminizem